Adsorption Studies of Ternary Metal Ions (Cs+, Sr2+, and Co2+) from Water Using Zeolite@Magnetic Nanoparticles (Z@Fe3O4 NPs) - Tung Van Nguyen; Lien Thi Nguyen; Ha Thi Thu Nguyen; Thu-Huong Le (Inorganics)
The mixture of three metal ions (Cs+, Sr2+, and Co2+) is commonly found in radioactive waste, which induces several negative health effects. The removal of multiple metal ions is a true challenge for researchers due to the competitive adsorption of ions onto adsorbents. In this study, three metal ions, namely Cs+, Sr2+, and Co2+, have been successfully removed simultaneously from water using zeolite@magnetic nanoparticles (Z@Fe3O4 NPs). The optimized condition for the adsorption of ternary metal ions was obtained at an adsorbent weight of 0.2, pH of 6.0~7.0, and contact time of 60 min. The adsorption mechanism of ternary metal ions onto the surface of Z@Fe3O4 NPs was studied using the Pseudo-first-order, Pseudo-second-order, Elovich, and Intra-particle diffusion models. The Dubinin–Radushkevich Temkin, Freundlich, and Langmuir isotherm models were used to study the isotherm adsorption. The ternary metal ion adsorption (Cs+, Sr2+, and Co2+) on Z@Fe3O4 NPs was followed by the Pseudo-second-order model (PSO) with correlation coefficient (R2) range of 0.9826–0.9997. Meanwhile, the adsorption isotherms of ternary metal ions on Z@Fe3O4 NPs were in line with the Langmuir model with R2 values higher than 0.9206, suggesting monolayer chemisorption with maximum adsorption capacities of 48.31, 15.02, and 10.41 mg/g for Cs+, Sr2+, and Co2+, respectively. Thus, the selectivity trend in the ternary metal ions system towards the Z@Fe3O4 NPs is observed to be Cs+ > Sr2+ > Co2+, which indicates that the competitive effect of Cs+ is the strongest compared to Sr2+ and Co2+ions.